2006
DOI: 10.1089/apc.2006.20.1
|View full text |Cite
|
Sign up to set email alerts
|

Dual Infection withMycobacterium tuberculosisandPneumocystis jiroveciLymphadenitis in a Patient with HIV Infection: Case Report and Review of the Literature

Abstract: We report a case of dual Mycobacterium tuberculosis (TB) and Pneumocystis jiroveci (carinii) (PCP) lymphadenitis in a patient with HIV who had been receiving trimethoprim-sulfamethoxazole (TMP-SMX) as systemic prophylaxis for PCP. This patient was successfully treated with antituberculosis medications and TMP-SMX. Our review of the literature identified this as the first reported case of dual TB and PCP lymphadenitis in an HIV-infected host and highlights the potential limitations of TMP-SMX prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Our literature review identified only a few reports: coinfection of a lymph node with T. marneffei and M. tuberculosis, 9 with T. marneffei and Mycobacterium intracellulare, 10 with Cryptococcus neoformans and mycobacteria, 11 and with M. tuberculosis and P. jirovecii. 12 In the present case, however, it is also possible that the lymph node involvement was secondary to septicemia.…”
Section: Discussionmentioning
confidence: 55%
“…Our literature review identified only a few reports: coinfection of a lymph node with T. marneffei and M. tuberculosis, 9 with T. marneffei and Mycobacterium intracellulare, 10 with Cryptococcus neoformans and mycobacteria, 11 and with M. tuberculosis and P. jirovecii. 12 In the present case, however, it is also possible that the lymph node involvement was secondary to septicemia.…”
Section: Discussionmentioning
confidence: 55%
“…It is worth mentioning that isolated P jiroveci lymphadenitis is rare but possible, with 25 cases reported from 1978 through 2006, ten of which had no pulmonary symptoms. 12 The differential diagnosis of gastrointestinal masses in AIDS patients primarily includes lymphoproliferative disorders, Kaposi sarcoma, and infectious causes. There was no morphologic evidence of lymphoproliferative disorders in our case.…”
Section: Pathology Findingsmentioning
confidence: 99%